3FAS Co. - Harris, Norfadila; Liban, Filzah Shazwani; Dahlan, Fatin Aisyah; Mohd Vickry, Siti Nursyafiqah; Ahmad Nasir, Anis Sobrina (2019)
Encouraged to create something is not exist in the market is not of our company's goals. Our company produce the auto shuttle collector machine in the market because our company want to consumer satisfaction when play the badminton sports. Our target is focusing on the citizen especially people who involves with badminton sports or loves to play the badminton. To ensure the our business start-up is well prepared, we provide all the important information in our business plan. Our company is considering many factors in order to achieve our objectives, mission, and vision. And also all member in the management are responsible to do their task in accordance with the schedule of tasks and responsibilities. This is because we are new company and also the our product is still new in the market, so our organization have done research and development process. It will help us to maintain business longer in the Malaysian market.